(untitled) (Research, Society and Development, 2021)
Considering that the timely correct diagnosis of a disease by the medical professional increases the chances of a faster cure and contributes to not having aggravations (sequelae), considering that there are several types of anemia and the increasingly frequent involvement in individuals, It is essential to assess knowledge about the topic among professionals in training. This study sought to comparatively analyze the concept of anemia, its types and differential diagnoses among medical interns at a faculty in Piauí, through a form with questions about concepts, types and differential diagnoses between anemias. Obtaining positive data on the level of knowledge of students, however there are not many similar scientific publications, which limits the comparison of results, however, it was evident that there is room for improvement, since the topic is quite comprehensive and important in a a country with such diversity and social inequalities as Brazil.